Depression and the incidence of urinary incontinence symptoms among young women: Results from a prospective cohort study. Issue 4 (August 2015) - Mishra, Gita D.; Barker, Megan S.; Herber-Gast, Gerrie-Cor; Hillard, Tim
<x xml:space="preserve">Abstract</x> Highlights Findings from this study suggest that depression is associated with the development of urinary incontinence symptom in young women. Women with a history of depression are at risk of developing urinary incontinence.